2019
DOI: 10.1016/j.amepre.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Dual Versus Never Use of E-Cigarettes Among American Indians Who Smoke

Abstract: Introduction: Many American Indian communities have a high prevalence of smoking and e-cigarette use, but factors associated with their dual use are rarely studied. Methods:In 2016, a total of 375 American Indian adults who smoke completed paper surveys regarding cigarette and e-cigarette use and provided saliva for cotinine levels. In 2018, cross-sectional analyses were performed, comparing dual users (12%), defined as using e-cigarettes on some or every day for the past 30 days, with never users of e-cigaret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Such patterns have been reported in other studies. 41 , 42 The impact of spousal behavior presents an opportunity for partner or family-based interventions that address the couple’s tobacco-related routines. 43 Self-reported psychiatric history was associated with an increased transition rate toward e-cigarette-only use, including from dual to e-cigarette-only use.…”
Section: Discussionmentioning
confidence: 99%
“…Such patterns have been reported in other studies. 41 , 42 The impact of spousal behavior presents an opportunity for partner or family-based interventions that address the couple’s tobacco-related routines. 43 Self-reported psychiatric history was associated with an increased transition rate toward e-cigarette-only use, including from dual to e-cigarette-only use.…”
Section: Discussionmentioning
confidence: 99%
“…There were limited studies that used HONC, particularly on the dual user status of adolescents. In adults, however, a small-scale study among native American dual users revealed the median score of HONC did not differ from that of exclusive cigarette users despite the perception of e-cigarette use to be less harmful than use of conventional cigarettes [ 28 ]. The lowest percentage of nicotine addiction in this study was that of the exclusive e-cigarette users (71.4%), and the highest prevalence of nicotine addiction was that of the dual users (97.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Methods regarding study design, setting, recruitment, and select measures have been previously reported [25, 26]. Methods pertinent to the current analyses are provided briefly below.…”
Section: Methodsmentioning
confidence: 99%